2017
DOI: 10.1002/bmc.4085
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomic analysis of serum reveals antifatigue effects of Yi Guan Jian on fatigue mice using gas chromatography coupled to mass spectrometry

Abstract: Yi Guan Jian (YGJ), one of the most commonly used traditional Chinese medicines, has been reported to possess significant antifatigue effects. However, the mechanisms underlying its antifatigue effects remain largely unresolved. In this study, a metabonomics approach, involving gas chromatography coupled to mass spectrometry and a multivariate statistical technique, was developed to estimate the extent to which YGJ alleviated the exhausting swimming-induced fatigue of mice. High-dose treatment with YGJ signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Chinese traditional medicine has its unique advantages in this respect. For example, except for the well-known Ginseng, some Chinese herbal formulas also have good antifatigue effects [3033]. Acupuncture is considered a beneficial alternative treatment to CRF in patients with breast cancer or undergoing anticancer therapy [34].…”
Section: Introductionmentioning
confidence: 99%
“…Chinese traditional medicine has its unique advantages in this respect. For example, except for the well-known Ginseng, some Chinese herbal formulas also have good antifatigue effects [3033]. Acupuncture is considered a beneficial alternative treatment to CRF in patients with breast cancer or undergoing anticancer therapy [34].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics, a novel technology of investigating endogenous small‐metabolites (MW < 1000) in biological systems, is widely applied to evaluate the metabolic profiling change induced by environmental and pathophysiological stimuli 18 . Compared with genes and proteins, metabolites can more directly reflect the patho/physiological state of tissue and cell during a biological event 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Modern research has found that Yi-guan decoction has anti-fatigue, anti-hypoxia, anti-inflammation, enhance the phagocytic function of phagocytic cells, effectively improve liver histopathological changes, improve liver inflammation, increase the content of serum albumin, promote ascites regression, and other effects. [ 24 26 ]…”
Section: Introductionmentioning
confidence: 99%